Grace Builds an Almost-Perfect Dog - Manley, Curtis; Subisak, Tracy (New York : Roaring Brook Press, 2025)
Grace programs a bit mischief into her perfectly behaved robot dog Kit, but a scary trip to the park highlights a bug in her code.
Ages 4-8.
Grades K-1.
Keywords: Robots -- Juvenile fiction; Dogs -- Juvenile fiction; Robotic pets -- Juvenile fiction; Programming (Computers) -- Juvenile fiction; Robots -- Fiction; Dogs -- Fiction; Robotic pets -- Fiction; Programming (Computers) -- Fiction; Picture books